AKTIVITAS GLUTATION PEROKSIDASE DAN KADAR GULA DARAH TIKUS DIABETES YANG DIBERI EKSTRAK DAUN KAPULAGA (Amomum cardamomum) - Hafsah Riyanti; Sorta Basar Ida Simanjutak; Hery Winarsi (Scripta Biologica, 2014)
Oxidative stress in a patient with diabetes known to decrease the activity of GSH-PX and increase the level of blood glucose. Glibenclamide is commonly used by patients with diabetes to lower the blood glucose. However, the long-term use of glibenclamide may induce the damage of pancreatic β-cells. The extract containing flavonoids and vitamin C of cardamoms leaf can reduce free radicals. The effect of cardamoms leaf extract on the enzymes activity and the level of blood glucose in diabetic rats is yet unknown. The aim of this study was to examine the effect of cardamoms leaf extract administration in the GSH-PX activities and the level of blood glucose of diabetic rats. The method used in this study was experimental with completely randomized design (CRD). There were three groups with five replicates for each. The first group, diabetic rats as control group were given no treatment; the second group, diabetic rats were given cardamoms leaf extract at the dose of 100 mg/kg of body weight; the third group, the diabetic rat were given glibenclamide at the dose of 2 mg/kg of body weight. Blood samples were taken three times at 0, 7, and 14 days after each treatment. Parameters measured were GSH-PX activity and the level of blood glucose. The data were analyzed using ANOVA F-test with a confidence level of 95%. The result of this study showed that the cardamoms leaf extract treatment decreased the activity of GSH-PX activity and decreased the level of blood glucose at a significant level (p < 0.05) from 278.8 to 101.4 mg/dl.